Optimization of L-asparaginase production from Escherichia coli using response surface methodology - Hien Trang, Nguyen Thi; Thanh Hoang, Le; Tuyen, Do Thi (Vietnam Journal of Biotechnology, 2020)
Among the antitumor drugs, bacterial enzyme L-asparaginase has been employed as the most effective chemotherapeutic agent in pediatric oncotherapy especially for acute lymphoblastic leukemia. In previous study, the L-asparaginase from Erwinia chrysanthermy was expressed in Escherichia coli BL21(DE3). The recombinant L-asparaginase was produced from recombinant E.coli BL21(DE3) under different cultivation conditions (inducer concentration, inoculum concentration and KH2PO4 concentration). The optimized conditions by response surface methodology using face centered central composite design. The analysis of variance coupled with larger value of R2 (0.9) showed that the quadratic model used for the prediction was highly significant (p < 0.05). Under the optimized conditions, the model produced L-asparaginase activity of 123.74 U/ml at 1.03 mM IPTG, 3% (v/v) inoculum and 0.5% (w/v) KH2PO4. Recombinant protein was purified by two step using gel filtration and DEAE chromatography. The purified L-asparaginase had a molecular mass of 37 kDa with specific activity of 462 U/mg and identified by MALDI-TOF mass spectrometry. Results of MALDI-TOF analysis confirmed that recombinant protein was L-asparaginase II. Recombinant L-asparaginase has antiproliferative activity with K562 cell line. In conclusion, this study has innovatively developed cultivation conditions for better production of recombinant L-asparaginase in shake flask culture.